Masking Subversion: Neocolonial Embeddedness in Anthropological Accounts of Indigenous Management - Banerjee, Subhabrata Bobby; Linstead, Stephen (Human relations (New York), 2004)
Sustainability and sound ecological management of the natural environment, allied to the expanding body of work on managing tacit and explicit knowledge, has led to an increased interest in the contribution which anthropology can make to the practical adaptation of indigenous environmental knowledge and practice to the improvement of organization in western societies. In an exemplary ethnographic study of an indigenous beaver trapper belonging to the Cree Nation, Whiteman and Cooper introduced the concept of ecological embeddedness. Their study could be considered a model that reverses the traditional practice of viewing managers as though they were primitives and applying concepts employed in studying native communities to organizations. They consider indigenous practitioners as managers, identify their management practices, and then reconsider contemporary management practice towards the environment in this light. They argue that to be ecologically embedded as a manager is to identify personally with the land, to adhere to beliefs of ecological respect, reciprocity and caretaking, actively to gather ecological information and to be located physically in the ecosystem. The present article provides a critique of Whiteman and Cooper’s argument and explores the ways in which, at the same time as it is purportedly represented, indigenous thought is masked and thereby subverted. We argue that much of their theorizing - as in so much anthropological accounting - is rooted in neocolonial thought and despite the authors’ claims, a so-called ‘indigenous land ethic’ has limited, if any, relevance to current management theory and practice. This is because such a land ethic is disembedded from the indigenous consciousness of their own economic, social and political history; and similarly for its reception requires a similar disembeddedness in the receiving culture - which then applies a loose analogy or even caricature of indigenous behaviour to its own practices. Such a consciousness remains, therefore, unreflexively embedded in its own neocolonialism. We argue that these problems are not confined to Whiteman and Cooper’s work, but are, to a greater or lesser degree, found in a wide range of anthropological accounts and constitute a problem with which the field is still struggling. To import these features into organizational theorizing without recognizing the deeply problematic nature of contemporary anthropological practice can only produce a reductionist and romanticized picture of native ontologies.